2007
DOI: 10.2465/jmps.050302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rate laws for the oxidation of five pyrites by dissolved oxygen in acidic solution

Abstract: Pyrites from five localities were oxidized with dissolved oxygen (DO) in acidic solution at 298 K. The objective of this study was to compare the oxidation rates of pyrite samples with different impurity contents. Initial conditions were a solution pH adjusted to approximately 4 and air saturation. DO, Fe 2+ , Fe(III) (as Fe 3+ and Fe(III) OH complexes), and SO 4 2− concentrations in the experimental solutions were periodically measured along with pH and redox potential (Eh). On the basis of the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…They provide some trace element concentrations, though they were unable to determine if the trace elements were in the pyrite or secondary phases; arsenic was not reported. Manaka (2007) reported that pyrite oxidation rate was positively correlated with impurity concentrations for five pyrites from different locations in experiments using dissolved oxygen as a reaction progress variable at pH 4. Impurities distributed in secondary sulfide phases were treated analytically in the same way as those in solid solution.…”
Section: Introductionmentioning
confidence: 97%
“…They provide some trace element concentrations, though they were unable to determine if the trace elements were in the pyrite or secondary phases; arsenic was not reported. Manaka (2007) reported that pyrite oxidation rate was positively correlated with impurity concentrations for five pyrites from different locations in experiments using dissolved oxygen as a reaction progress variable at pH 4. Impurities distributed in secondary sulfide phases were treated analytically in the same way as those in solid solution.…”
Section: Introductionmentioning
confidence: 97%
“…2.10). The obtained values in this study are in the same order as the values reported by Smith and Schumate (1970) who found a value of 0.7 for a mixture of pyrite and marcasite, or Kamei and Ohmoto (2000), Manaka et al (2000), and Manaka (2007) with values from 0.5 to 1 for pyrite, or McKibben (1984), Williamson and Rimstidt (1994) and Domènech et al (2002) for pyrite (0.4-0.5±0.04) at pH 2-10. In the case of arsenopyrite, the obtained value is higher than those reported by Yu et al (2007)…”
Section: The Effect Of Dissolved Oxygen On Dissolution Ratessupporting
confidence: 89%
“…Two additional cases were considered to investigate WRPs with lower and higher reactivity for the same temperature scenarios, which was achieved by decreasing or increasing the reference pyrite reaction rate constant by one order of magnitude, respectively. These modifications to the rate constant were selected based on literature values reported by Lefebvre et al (2001) and Manaka (2007). All cases were simulated with for well-aerated conditions (assuming a fixed pO 2 at atmospheric levels).…”
Section: D Model Descriptionmentioning
confidence: 99%
“…The porous medium properties of waste rock based on theNoel and Ritchie (2012) andPantelis et al (2002); the heat transport parameters are chosen at the midpoints of literature values fromPantelis et al (2002); the chemical parameters as well as gaseous diffusion coefficient are constrained by literature values reported inLefebvre et al (2001) andManaka (2007). Optimal temperature for microbial activity was obtained fromXie et al (2007).…”
mentioning
confidence: 99%